Feeding ecology of Neoarius leptaspis in the Rawa Biru Lake, Merauke, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wibowo DN, Rukayah S, Wahayu NL, Mote N. 2022. Feeding ecology of Neoarius leptaspis in the Rawa Biru Lake, Merauke, Indonesia. Biodiversitas 23: 1327-1335. A few studies have been carried out on Neoarius leptaspis (Bleeker, 1862), however, its feeding ecology was not examined, especially for the sample from Rawa Biru Lake, Merauke, Papua, Indonesia. Therefore, this study aims to analyze the feeding ecology of N. leptaspis at 8 sampling sites in the lake, which were sampled in the morning and evening. The parameters observed were natural food diversity, mouth width ratio, intestine length ratio, stomach fullness and content, preponderance index, and electivity index. The result showed that 25 plankton species were observed in the waters. Neoarius leptaspis has a mouth width ratio of approximately 75% of head width. The full stomach was observed in the samples collected in the evening, where the diets were dominated by animal materials as indicated by the indexes of preponderance and electivity. The mouth width ratio, feeding periodicity, intestine length, and dominant diets were similar to the previous reports on the same species from other regions. This showed that N. leptaspis is a predatory fish species based on the feeding ecology data, which provides essential information for fisheries and conservation.
Keywords: Ariidae; catfish; food habit; lake; trophic level